Pengaruh Penggunaan Concept Mapping Terhadap Kemampuan Berpikir Kritis Siswa Mata Pelajaran IPA SD Kota Bengkulu - Lia Refika; Endang Widi Winarni; Feri Noperman (JURIDIKDAS, 2023)
This study aims to determine the effect of the use of Concept Mapping applied to the Problem Based Learning model of critical thinking skills of students of science class V SD Bengkulu City. This research is a quantitative research. The type of research used is quasi experimental research with the design of The Matching-Only Pretest-Posttest Control Group Design. The population in this study is all students of grade V SD Bengkulu City. The sampling technique used Two Stage Random Sampling so as to obtain the class VA SDN 41 Bengkulu City as the experimental class and class VB SDN 82 Bengkulu City as the control class. The research instrument is a critical thinking skill test which is about essay given through pretest and posttest. Based on the hypothesis test using t-test of two independent samples, obtained tcount (2.95) > ttable (1.67) at 5% significant level, it can be concluded that there is influence of Concept Mapping usage applied in Problem Based Learning model to ability critical thinking students of science class V SD Bengkulu City.